A bio-guided approach for the development of a chestnut-based proanthocyanidin-enriched nutraceutical with potential anti-gastritis properties. (August 2018) - Sangiovanni, Enrico; Piazza, Stefano; Vrhovsek, Urska; Fumagalli, Marco; Khalilpour, Saba; Masuero, Domenico; Di Lorenzo, Chiara; Colombo, Luca; Mattivi, Fulvio; De Fabiani, Emma; Dell'Agli, Mario
Graphical abstract: Abstract: Gastritis is a widely spread inflammatory disease, mostly caused by Helicobacter pylori infection. Release of IL-8 by the stomach epithelium is a hallmark of gastritis and contributes to the amplification of the inflammatory state. Pharmacological modulation of IL-8 release is a strategy to relieve gastric inflammation and prevent more severe clinical outcomes. In search of nutraceuticals with potential anti-gastritis properties we used a bio-guided approach based on IL-8 secretion by gastric cells to characterize extracts from the fruits of different chestnut varieties. We found that the ability to inhibit IL-8 secretion correlated with the amount of proanthocyanidins and was associated to the not edible parts of chestnut in all the tested varieties. We also found that the anti-inflammatory activity is preserved upon mild thermal treatment and after in vitro simulated gastric digestion. By combining a robust bio-guided approach with a comprehensive analysis of the tannin fraction of chestnut extracts, we provide evidence for the potential use of chestnut-based nutraceuticals in human gastritis. The bioactive components of chestnut fruits inhibit IL-8 secretion by impairing NF-κB signaling and by other mechanisms, thus opening new applications of proanthocyanidins for inflammation-based diseases.